2007
DOI: 10.1038/nn1877
|View full text |Cite|
|
Sign up to set email alerts
|

Functional dissection of circuitry in a neural integrator

Abstract: In neural integrators, transient inputs are accumulated into persistent firing rates that are a neural correlate of short-term memory. Integrators often contain two opposing cell populations that increase and decrease sustained firing as a stored parameter value rises. A leading hypothesis for the mechanism of persistence is positive feedback through mutual inhibition between these opposing populations. We tested predictions of this hypothesis in the goldfish oculomotor velocity-to-position integrator by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
166
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(183 citation statements)
references
References 50 publications
12
166
0
Order By: Relevance
“…Crawford and Vilis (1993) provided evidence for multiple vertical/torsional integrators when they pharmacologically inhibited the integrator and found that the eye did not drift to a single resting position, but rather, multiple resting positions were possible. Recent experimental findings in goldfish also support the hypothesis of separate integrators for horizontal gaze (Aksay et al 2007). …”
Section: Multiple Horizontal Nismentioning
confidence: 65%
“…Crawford and Vilis (1993) provided evidence for multiple vertical/torsional integrators when they pharmacologically inhibited the integrator and found that the eye did not drift to a single resting position, but rather, multiple resting positions were possible. Recent experimental findings in goldfish also support the hypothesis of separate integrators for horizontal gaze (Aksay et al 2007). …”
Section: Multiple Horizontal Nismentioning
confidence: 65%
“…The small effect seen on activity with contralateral inhibition (Extended Data Figs 2e, 8d) implies further that ALM hemispheres function as "modules", maintaining preparatory activity independently 28 . After unilateral perturbation, information from the unperturbed side helps recover function of the perturbed side.…”
Section: Contralateral Input Is Required For Recoverymentioning
confidence: 94%
“…Despite extensive efforts to identify biological persistent activity modes mediated by recurrent excitatory synaptic connections 48 , very little experimental evidence supports the classic hypothesis that reverberant network activity functions to encode and maintain information proposed by Hebb 9 . Our finding that sequential stimulation did not reset hilar persistent activity to a new state corresponding to the most recent stimulus is also inconsistent with the predictions from theoretical studies employing attractor-based networks with recurrent connectivity 49 .…”
Section: Relationship To Delay-period Activity Recorded During Workinmentioning
confidence: 99%